OPTIMALISASI PENGGUNAAN MIND MAPPING DALAM MENINGKATKAN KREATIVITAS SISWA DI MADRASAH - Astindari, Tri; Fajri, Zaenol; Rosyidah, Infitahur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Creative and innovative learning is key to enhancing students’ understanding of lesson materials. One effective method is mind mapping, which allows students to organize ideas visually and better comprehend complex concepts. This study aims to analyze the effectiveness of mind mapping in enhancing students’ creativity in the learning process. Additionally, it identifies the challenges and benefits students experience when applying this method in their learning activities. This research employs a qualitative approach using observation, interviews, and documentation methods. Observations were conducted to directly assess students’ activities in using mind mapping during lessons. Interviews were carried out with teachers and students to gain insights into the effectiveness of this method. Documentation was used as supplementary data collection, including students’ completed mind maps. The findings indicate that mind mapping enhances students' creativity in understanding lesson materials. Students become more active in developing new ideas and connecting previously learned concepts. Moreover, this method helps improve students’ memory retention as information is presented in an engaging visual format. However, some challenges were identified, such as time constraints in creating mind maps and certain students’ difficulties in organizing concept maps effectively. Therefore, further guidance from teachers is necessary to ensure students can fully utilize this method. In conclusion, mind mapping is an effective technique for fostering students’ creativity, though it requires adequate support and training for optimal implementation. As a recommendation, teachers should integrate mind mapping regularly into lessons and provide additional guidance to help students become more accustomed to and proficient in using this method.